2015
DOI: 10.1371/journal.pone.0129076
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal pH and Transit Time Profiling in Healthy Volunteers Using the IntelliCap System Confirms Ileo-Colonic Release of ColoPulse Tablets

Abstract: IntroductionColoPulse tablets are an innovative development in the field of oral dosage forms characterized by a distal ileum and colon-specific release. Previous studies in humans showed release in the ileo-colonic region, but the relationship between gastrointestinal pH and release was not experimentally proven in vivo. This information will complete the in vivo release-profile of ColoPulse tablets.Materials and MethodsRelease from ColoPulse tablets was studied in 16 healthy volunteers using the dual label i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 24 publications
3
80
0
3
Order By: Relevance
“…For instance, the difference in pH from the lower stomach to the small intestine is from ~2.5 to ~7 respectively. [28] If a classic [4:6] turn is not tolerated at the position of mutation, it was found that adding two or four glycines on either side ( G2_pHSW and G4_pHSW ) provides 10 – 14 residue loops that still function as a pH switch, these could be used as loop and β-turn replacements in other β-sheets. Our pH dependent conformational switch is small, uses natural amino acids and operates under mild conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the difference in pH from the lower stomach to the small intestine is from ~2.5 to ~7 respectively. [28] If a classic [4:6] turn is not tolerated at the position of mutation, it was found that adding two or four glycines on either side ( G2_pHSW and G4_pHSW ) provides 10 – 14 residue loops that still function as a pH switch, these could be used as loop and β-turn replacements in other β-sheets. Our pH dependent conformational switch is small, uses natural amino acids and operates under mild conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal pH profiling and dosing was performed by IntelliCap System ® capsules (~size 000 containing ~184 μ L), which are approved for clinical use for profiling (Maurer et al. ) and drug delivery (Becker et al. ) by operator‐controlled computer monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…Intestinal pH in cynomolgus has not been previously reported. Intestinal pH profiling and dosing was performed by IntelliCap System â capsules (~size 000 con-taining~184 lL), which are approved for clinical use for profiling (Maurer et al 2015) and drug delivery (Becker et al 2014) by operator-controlled computer monitoring. Nine monkeys (six fasted o/n and three fed) were given empty IntelliCap System â capsules (~size 000) by oral dosing for profiling gastrointestinal pH.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Targeting small molecule delivery to the large intestine is challenging because the vector has to avoid absorption in the small intestine, resist digestion by brush-border and exocrine enzymes and thereafter selectively release its small molecule payload in the large intestine. Techniques for small molecule colonic delivery such as encapsulation, using fermentable polymer coatings, 23 pH and/ or time-dependant release 24 and direct instillation, using SCFA enema 25 are limited to relatively low dosing regimens or are unsuitable for population-level interventions. The binding affinity between FFAR and SCFA appears adapted for the relatively high SCFA concentrations found in colonic environment, resulting to a key specification of any colonic delivery system for SCFA: it must be capable of inducing significant change in the large colonic SCFA pool.…”
Section: Introductionmentioning
confidence: 99%